The Pandemic's Effect on Demand for Public Schools, Homeschooling, and Private Schools - Tareena Musaddiq; Kevin Stange; Andrew Bacher-Hicks; Joshua S. Goodman (Center for Economic Studies and ifo Institute (CESifo), 2021)
The Covid-19 pandemic drastically disrupted the functioning of U.S. public schools, potentially changing the relative appeal of alternatives such as homeschooling and private schools. Using longitudinal student-level administrative data from Michigan and nationally representative data from the Census Household Pulse Survey, we show how the pandemic affected families' choices of school sector. We document four central facts. First, public school enrollment declined noticeably in fall 2020, with about 3 percent of Michigan students and 10 percent of kindergartners using other options. Second, most of this was driven by homeschooling rates jumping substantially, driven largely by families with children in elementary school. Third, homeschooling increased more where schools provided in-person instruction while private schooling increased more where instruction was remote, suggesting heterogeneity in parental concerns about children's physical health and instructional quality. Fourth, kindergarten declines were highest among low income and Black families while declines in other grades were highest among higher income and White families, highlighting important heterogeneity by students' existing attachment to public schools. Our results shed light on how families make schooling decisions and imply potential longer-run disruptions to public schools in the form of decreased enrollment and funding, changed composition of the student body, and increased size of the next kindergarten cohort.
Keywords: I20; I24; 330